2012
DOI: 10.1093/molbev/mss269
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Isopenicillin N Synthase in an Animal Genome

Abstract: Horizontal transfer of genes is widespread among prokaryotes, but is less common between microorganisms and animals. Here, we present evidence for the presence of a gene encoding functional isopenicillin N synthase, an enzyme in the β-lactam antibiotics biosynthesis pathway, in the genome of the soil-living collembolan species, Folsomia candida (FcIPNS). At present, this gene is only known from bacteria and fungi, as is the capacity to produce β-lactam antibiotics. The FcIPNS gene was located on two genomic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 35 publications
1
44
0
Order By: Relevance
“…A variety of genetic mechanisms giving rise to new genes have been identified, including gene duplication, gene fusion and fission, exon shuffling, de novo origination from previously non-coding sequences and horizontal gene transfer [26]. Recently, we have identified horizontal gene transfer as a genetic mechanism that explains the presence of unique functional genes in collembolans [96]. The fact that F .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of genetic mechanisms giving rise to new genes have been identified, including gene duplication, gene fusion and fission, exon shuffling, de novo origination from previously non-coding sequences and horizontal gene transfer [26]. Recently, we have identified horizontal gene transfer as a genetic mechanism that explains the presence of unique functional genes in collembolans [96]. The fact that F .…”
Section: Discussionmentioning
confidence: 99%
“…The fact that F . candida is the first animal that is equipped with a biosynthesis pathway for β-lactam antibiotics [96] underpins the importance of such evolutionary processes in this animal group.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we applied in situ hybridization to show that ACVS is localized and strongly induced in the gut epithelium of the animal (Nota et al, 2008). Furthermore, Roelofs et al (2013) showed that the formation of a beta-lactam can be catalyzed by beta-lactam biosynthesis genes belonging to the genome of Folsomia . Very recently, we detected and quantified beta-lactam compounds in Folsomia using an ELISA assay in vivo , and preliminary data show that this metabolite increases in abundance after heat shock treatment (W.S., unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Biosynthesis of these compounds has been described in several species of Actinobacteria and Proteobacteria and in several fungi (Ozcengiz and Demain, 2013). It was not reported in animals until recently, when the first metazoan beta-lactam biosynthesis genes were characterized in the springtail Folsomia candida (Roelofs et al, 2013). Folsomia candida is a soil-dwelling basal hexapod, the closest relatives of the insects (Misof et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation